Assessment of awareness and willingness to use pre-exposure prophylaxis for HIV prevention among female sex workers in Rwanda: a cross sectional study - Nzungize, Albert; Munyaneza, Athanase (Frontiers in Public Health, 2025)
BackgroundFemale sex workers (FSWs) in sub-Saharan Africa bear a disproportionate burden of HIV acquisition. While pre-exposure prophylaxis (PrEP) is increasingly accessible in the region, limited data exist on FSWs awareness of and willingness to use PrEP. This study aimed to assess PrEP awareness and willingness to use it, along with associated factors, among FSWs in Kigali, Rwanda.MethodsThis cross sectional study, conducted from April to September 2024, evaluated PrEP awareness and willingness to use it among 333 FSWs over 18 years of age recruited through community based FSW associations. Using a stratified random sampling technique, survey data were analyzed using SPSS, with logistic regression employed to explore associations between participant characteristics and PrEP awareness and willingness. Ethical approval was obtained from the Rwanda National Ethics Committee.ResultsThe mean age of participants was 30 years (SD: 7.26), with 47% aged between 25 and 34. Most were single (67%) and unemployed (66%), with nearly half (49.5%) reporting only primary education. A significant proportion (81%) had undergone HIV testing in the past 6 months, and 50% had been involved in sex work for 2 to 5 years. The median number of sexual partners in the past week was 7. Awareness of PrEP was high (81%), however, among those who reported consistent condom use were less likely to be aware of PrEP [adjusted odds ratio (aOR): 0.40, 95% confidence interval (CI): 0.19, 0.83], as were those not screened for sexually transmitted infections (STIs) compared to those who were screened (aOR: 0.43, 95% CI: 0.22, 0.85). Willingness to use PrEP was reported by 80% of participants. Those with a primary education were more willing to use PrEP compared to those with no formal education (aOR: 4.09, 95% CI: 1.62, 10.33). Conversely, participants who were screened for STIs were less likely to report willingness to use PrEP compared to those who were not screened (aOR: 0.28, 95% CI: 0.12, 0.62).ConclusionThis study demonstrates high awareness and willingness to use PrEP among FSWs in Kigali. However, among those who reported consistent condom use and those unscreened for STIs were less aware of PrEP, and willingness to use it varied based on education and STI screening status. These findings underscore the need for targeted health education and STI screening initiatives to enhance PrEP uptake and strengthen HIV prevention efforts in this vulnerable population.